Performance of Public Elementary School Teachers: Effects of Discipline and Work Environment - Yanti, Aprilia Rudi; Sodirin, Sodirin (Ensiklopedia: Jurnal Pendidikan dan Inovasi Pembelajaran Saburai, 2024)
Some problems that are still often found in schools include teachers who still come late, less than optimal attendance percentage, a work environment with a narrow and uncomfortable work space, noise that is seen from traders who enter the school environment to offer products so that it can disrupt teaching and learning activities and disrupt work activities, and many more. This problem is also still found in SDN 04 Jatimulyo, South Lampung. Therefore, the purpose of this study is to see the effect of discipline and work environment on teacher performance at SDN 04 Jatimulyo, South Lampung. The population in this study were all teachers of SDN 04 Jatimulyo, South Lampung with sample determination using the total sampling technique, so that a sample of 33 people was obtained. Based on the results of the analysis, discipline and work environment have a positive effect on the performance of teachers at SDN 04 Jatimulyo, and simultaneously affect the performance of teachers at SDN 04 Jatimulyo.